Navigating the Digital Age: The Need for Android-Based Learning Media in Technology and Educational Media Courses - Muh. Yamin; Sahlan, Muh Fadli Fauzi; Fakhrunnisaa, Nur (Educational Journal of Learning Technology, 2023)
The objective of this study is to ascertain the assessment of student requirements for Android-based instructional media, particularly in the domains of technology and educational media courses. The employed research methodology is quantitative. The participants of this study were derived from a sample size of 70 individuals enrolled in the second semester of the Islamic education management study program at IAIN Palopo. The research instrument employed in this study is a questionnaire comprising 14 items and statements that pertain specifically to learning requirements utilizing Android-based media. The findings of this study demonstrate the necessity and popularity of including Android-based press, particularly in educational media and technology courses. Additionally, the availability of resources for using Android-based media has been adequately met.